Analisis Makroskopis dan Mikroskopis Daun Dollar (Zamioculcas zamiifolia (Lodd.)) - Surahmaida; Aurelia Nabila Salsa Putri Bogar (Jurnal Penelitian Pendidikan IPA, 2025)
The dollar plant (Zamioculcas zamiifolia (Lodd.)) shows significant potential for medicinal applications. Despite numerous studies examining the chemical components in dollar plant leaves, there is still insufficient research on their macroscopic and microscopic features. This research was carried out to recognize and detail the macroscopic and microscopic characteristics of the dollar plant leaves and their powder simplisia. This qualitative descriptive study included processes like identifying plants, preparing simplisia, and conducting both macroscopic and microscopic observations. The macroscopic examination emphasized the observation of the leaf's shape, dimensions, and hue, while the microscopic examination sought to recognize anatomical characteristics such as stomata, trichomes, vascular bundles, and calcium oxalate crystals. The research showed that the dollar plant's leaves are a dark green color, glossy, smooth, elongated, featuring flat edges, pointed ends, and rulvunded bases. Under the microscope, the leaves displayed paracytic stomata type, spiral transport bundles, unicellular trichomes, and needle- shaped calcium oxalate crystals. Additional studies on the characterization of other componentsof the dollar plants including stem and roots, for a more complete characterization.